William Faulkner’s Environmental Awareness in His Go Down, Moses - Agustin, Suciati; Najma, Eva (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Andalas, 2021)
This article analyzes William Faulkner’s novel entitled Go Down, Moses. The aim of this research is to scrutinize the author’s environmental awareness which he expresses through Isaac McCaslin (Ike), the main character of the story. The data is analyzed through qualitative method, and the result is presented using descriptive method. The source of primary data is Go Down, Moses novel and the sources of secondary data are books, journal articles, speech and interview scripts related to the topic of the research. The writer applies ecocritical theory specifically Aldo Leopold’s Land Ethic. The findings shows that there are three forms of William Faulkner’s environmental awareness that he expresses in this novel. They are Understanding the equality of human and nature; loving and respecting nature; and being aware of nature protection and preservation.